Decellularization Strategies for Regenerating Cardiac and Skeletal Muscle Tissues - Tan, Yong How; Helms, Haylie R.; Nakayama, Karina H. (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiovascular disease is the leading cause of death worldwide and is associated with approximately 17.9 million deaths each year. Musculoskeletal conditions affect more than 1.71 billion people globally and are the leading cause of disability. These two areas represent a massive global health burden that is perpetuated by a lack of functionally restorative treatment options. The fields of regenerative medicine and tissue engineering offer great promise for the development of therapies to repair damaged or diseased tissues. Decellularized tissues and extracellular matrices (ECMs) are cornerstones of regenerative biomaterials and have been used clinically for decades and many have received FDA approval. In this review, we first discuss and compare methods used to produce decellularized tissues and ECMs from cardiac and skeletal muscle. We take a focused look at how different biophysical properties such as spatial topography, ECM composition, and mechanical characteristics influence cell behavior and function in the context of regenerative medicine. Lastly, we describe emerging research and forecast the future high impact applications of decellularized cardiac and skeletal muscle that will drive novel and effective regenerative therapies.